The Plurality of Languages and Literature in Translation: The Post-Colonial Context - Choudhuri, Indra (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1997)
AbstractLinguistic pluralism in India is not a sign of social and cultural fragmentation but rather a positive force, a recognition of the differences which constitute the nation. This recognition needs to be extended beyond the languages recognized in the Indian Constitution to those which create an intermediary space, thereby subverting received hierarchies.